The Heartguard: A Humanitarian Pediatric Cardiac Surgery Program in Rural China - Zhang, Xun E.; Geng, Zhi; Shao, Jun; Yao, Hao; Wang, Lu; Li, Xiaobo; Li, Qingguo (The Thoracic and Cardiovascular Surgeon, 2021)
Background Congenital heart disease (CHD) accounts for the most common birth defects in China, pressuring both the physical and mental health in children. The inaccessibility of CHD children in rural China due to financial difficulties is demanding inputs from both the government and society. The Heartguard project is a program developed to improve the delivery of CHD care in rural China.Methods The Heartguard project partners with county hospitals and performs CHD screening to diagnose patients with CHD in rural China. Diagnosed children with CHD who are unable to afford therapy will subsequently receive treatment sponsored by the financial partners. All patients are followed up by the local partner and visiting surgical team members.Results More than 10,000 children across 9 provinces underwent CHD screening. A total of 240 (accounting for an incidence of 2.4%) was treated by the program, of which 226 patients were managed invasively, the other 14 patients conservatively. Open surgery was performed in 162 patients, while endovascular procedures were applied in another 64. No mortality or significant complications occurred during the transfer. There was no perioperative or late death.Conclusion This humanitarian cardiac surgery program is able to promote accessibility of care for CHD children in rural China. The quality of life of these patients can be improved with continuous input from the society.
Keywords: congenital heart disease; CHD; cardiac; cardiac catheterization/intervention; surgery/incisions